Iris in images preparation identificaton - Рябова, Любовь Владимировна; Самойленко, Мария Евгеньевна; Бойко, Юлия Петровна (Ukrainian Information Security Research Journal, 2016)
The method for the rapid determination of the digital image of the eye center point lying inside the pupil, which can then be used as the approximate center of the region of its small size. The method is based on the binarization image, followed by the search of the pupil detector Kenny. For the preparation of the pupil with a view to removing it from the original image using the selected path. An alternative method of image ireparirovaniya iris due to precise positioning of the object partially closed opaque mask. To carry out numerical experiments in a database used by the public eye image database CASIO.